Valor unsung heroes from Iraq, Afghanistan, and the home front - Greenblatt, Mark Lee 1973- (Taylor Trade Publishing, an imprint of Rowman & Littlefield, 2014)
Valor features the thrilling stories that are the fruit of Mark Lee Greenblatt s interviews with brave American servicemen from twenty-first-century wars. These soldiers, sailors, and Marines have risked their lives several times over for their country as well as for their fellow troops and civilians. Still, until now, their stories have largely gone unnoticed by the public, perhaps lost in the frenzied and often nasty debate surrounding those conflicts. As the author writes, This generation does not have an Audie Murphy. I set out to change that with this book. Detailing incredible and evocative feats including an Army pilot who rescued two fellow pilots from a deadly crash in hostile territory and strapped himself to the helicopter s exterior for the flight to the hospital Greenblatt provides glimpses into the minds of these men as they face gut-wrenching decisions and overcome enormous odds. However, this book is much more than tales of riveting action. Each chapter goes beyond linear combat stories to explore each hero s motivations, dreams, and the genuine emotions that were evoked in the face of extreme danger. Readers will be transported to a variety of settings from close-quarters urban fighting in Iraq to mountainside ambushes in rural Afghanistan to a midnight rescue in the middle of the Atlantic as they accompany the men who do not see themselves as heroes but as patriots in the line of duty. As the author writes, "This generation does not have an Audie Murphy. I set out to change that with this book."